OUTCOME BASED EDUCATION (OBE) IS NEED OF THE HOUR - Thirumoorthy, G. (International Journal of Research -GRANTHAALAYAH, 2021)
Educational objectives are soul for any educational Programme and it is the prime pillar for sustainable socio-economic development. The holistic educa- tional objectives need to changes according to the social change. To achieve the holistic educational objectives the educational opportunities were decentral- ized; as a result, worldwide the rate of literates and the percentage of educated people are increased; especially in India was successfully achieved elementary, secondary, and higher education too. Further, the new education policy-2020 insisted to increase the enrolment ratio in higher education from 26.3% (2018) to 50% by 2035. Along with the objectives of increasing the quantitative stu- dents’ enrolment percentage in higher education, it is the need of the hour to insist on outcome-based education (OBE) for holistic development. Keeping these as a background the researcher intended to describe the OBE as a need of the hour.